Rational education on the use of drugs and self-examination of cholesterol levels for the people of Makassar City - Yuniharce Kadang; Zulfiah (Abdimas Polsaka, 2025)
Health problems due to high cholesterol levels in the blood are a big challenge for the people of Indonesia, especially in urban areas such as Makassar. High cholesterol is closely related to an increased risk of cardiovascular disease, stroke, and other metabolic complications. On the other hand, the public's understanding of the rational use of drugs is still limited, so it has the potential to cause side effects, drug resistance, and decreased therapy effectiveness. The method of implementing the activity consisted of educational counselling related to the classification of drugs, how to use, store, and dispose of drugs correctly, as well as demonstrations of the use of cholesterol checkers (Easy Touch) using the Point of Care Testing (POCT) method. In addition, participants were given insight into the risk factors for high cholesterol and their control strategies, such as a healthy diet, exercise, and regular check-ups. The activity results showed high enthusiasm and participation of participants in the discussion and practice sessions. Brief evaluations through question-and-answer methods indicated increased participants' understanding of the importance of rational medication use and initial skills in independent cholesterol examination. This activity not only fosters health awareness but also strengthens the function of the Tri Dharma of Higher Education in community service. Thus, this activity contributes to increasing public health literacy and encouraging a healthy lifestyle to reduce the prevalence of non-communicable diseases in urban areas.